DRUG UTILIZATION PATTERN IN INDOOR PATIENT OF RADIOTHERAPY DEPARTMENT AT A TERTIARY CARE HOSPITAL IN SOUTHERN RAJASTHAN - RAHUL DAMOR; MEENA ATRAY; RAMKIRAN NV; CHETAN JANI; HARSH K BRAHMBHATT; ARVIND SINGH TANWAR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The study was planned to evaluate on drug utilization pattern of drug use in the indoor of radiotherapy department, using the World Health Organization recommended core drug use indicators, to compare the cost of drug used and to provide feedback to the concerned department to improve rational prescribing. Methods: Four hundred and five newly diagnosed cases of cancer with age more than 18 of both genders were included in the study. The demographic data, diagnosis, group of anticancer drugs, individual anticancer drug, combinations of anticancer drugs, and cost of drug reactions were recorded and analyzed statistically, using descriptive study statistics. Results: Cervical cancer (19.51%) was the most frequently diagnosed cancer, followed by lung cancer (17.04%). Platinum compounds (76.30%) were maximum utilized group of drugs. Carboplatin was the most commonly prescribed drug (53.09). Average number of drugs prescribed per prescription was 8.77. Carboplatin + Paclitaxel combination was the most commonly prescribed combination. Pantoprazole was maximally used adjuvant drug. Conclusion: About 100% of drugs were prescribed by generic name and 86.27% of drugs were prescribed from National List of Essential Medicines of India, 2022 indicates rational prescribing. The cost of anticancer drugs was much less in comparison to other studies.